The Edinburgh companion to the Bible and the arts - Prickett, Stephen (Edinburgh : Edinburgh University Press, 2014)
Examines the changing relationship between the Bible and the arts, showing how the arts portray biblical stories in various ways and through various media, and how 'the' Bible is actually multiple entities: fiercely contested translations in many languages. Generously illustrated with examples including painting, architecture and stained glass.
INSPIRATION AND THEORY -- 'What has Athens to do with Jerusalem?' The Biblical Chain-Gang / Stephen Prickett -- Hebrew Aesthetics and Jewish Biblical Exegesis / Mordechai Z. Cohen -- Migne's Achievement and the Modern Transmission of Ancient Manuscripts / D.H. Williams -- Augustine on Beauty : a Biblical Aesthetics / David Lyle Jeffrey -- Sublimity and Resistance to Form in the Early Modern Bible / Anthony Ossa-Richardson -- 'A Babel of Bibles' : Aesthetics, Translation and Interpretation since 1885 / Nicholas Bielby -- Lest the Story be Lost : Biblical Fiction / David Dickinson -- Bible and Phenomenology / Kevin Hart -- ART AND ARCHITECTURE -- Gospel of John in Early Christian Art / Robin M. Jensen -- Images of Conflict : the art of Anti-Judaism in Fifth Century Rome / Geri Parlby -- Shared Tradition : The Decorated Pages of Medieval Bibles and Qurʹans / Vivian B. Mann -- Speaking Pictures : Medieval Religious Art and its Viewers / Charles Moseley -- Iconography of the Cross as the Tree of Life / Christopher Irvine -- Art and the Resurrection Narrative / Christopher Herbert -- Covenants and Connections : the Sassetti Chapel, Santa Trinita : Scenes from the Life of St Francis, Ghirlandaio, 180-85 / Chloë Reddaway -- Who Framed Bathsheba? / Vivienne Westbrook -- Fresco Decoration in the Sistine Chapel : Biblical Authority and the Church of Rome / Shirley Smith -- Materiality and Iconography of the Coverdale Bible (1535) Title Page in Context / Mark Rankin and Guido Latré -- Moses in Eighteenth Century Art / Nigel Aston -- Blake : Text and Image / Christopher Rowland -- 'For Thine is the Kingdom' : Portraying the Bible in Nineteenth-Century Stained Glass / Christopher Rogers -- Van Gogh : Framing a Biblical Vision / Daphne Lawson -- Coventry Cathedral : Conception and Reality / Sarah Hosking -- LITERATURE -- Sacred Poetry : Watts and Wesley / J.R. Watson -- Bible Interpreted by Hymns / Robin Gill -- Art of Unveiling : Biblical Apocalypse / Christopher Burdon -- Divine Comedy as the Word of God / Patricia Erskine-Hill -- Medieval Bible as Literature / Alastair Minnis and A.B. Kraebel -- Homer Writes Back : Rhetorical Art and Biblical Epic Justice in Paradise Lost / Phillip J. Donnelly -- Biblical and Seventeenth-Century Poetry : The Case of the Psalms and George Herbert / Christopher Hodgkins -- From Virtue to Goodness : Biblical Values in Victorian Literature / Jan-Melissa Schramm -- Mirror of the Law of Liberty : Reflecting the Hidden Christ in George Macdonald's Lilith / Bethany Bear -- Figurative Literalism : The Image of the Creator in Nineteenth-Century British Literature / Norbert Lennartz -- From Satire to Sanctity : The Prophetic Books in T.S. Eliot's Poetry / Jan Gorak -- Imitatio Pilati et Christi in Modern Historical Drama / James Alexande--
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Bibeln; Bibel; Arts in the Bible; Christian art and symbolism; Arts dans la Bible; LITERARY CRITICISM / Reference; Arts in the Bible; Christian art and symbolism; Architektur; Kunst; Künste; Literatur; Rezeption; Rezeption; Ästhetik; Kunst; Architektur; Literatur; Künste; Historiska händelser i Bibeln; Kristen konst och symbolik; Bibliska motiv i litteraturen; Bibliska motiv i konsten; Estetik -- religiösa aspekter; Religion; Electronic book